Metacompetencies for the future workforce: An analysis of generation Z's work readiness in the VUCA workplace - Mujib, Miftachul; Widayanti, Ipuk; Ratnawati, Shinta; Agustin, Hesti; Ernawati, Nimas Jimi (Nur Science Institute, 2026)
This study aimed to explore how metacompetencies influence the work readiness of Generation Z in Indonesia and to investigate the moderating effect of prior work experience. The originality of this research lies in its application of Shet’s (2024) VUCA-oriented metacompetency framework within the Indonesian workforce context. Adopting a quantitative explanatory approach, the study gathered data from 125 Generation Z workers aged 17-28 across Indonesia, collected between July and August 2025. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique by SmartPLS 4 software, complemented by Multi-Group Analysis (MGA) to examine both direct causal relationships and the moderating influence of work experience. The results reveal that cognitive, cross-cultural, and personal effectiveness competencies significantly enhance work readiness, while analytical competency shows no significant effect. Work experience moderates these relationships, strengthening the influence of metacompetencies on readiness. Practically, the findings guide educators, employers, and policymakers to prioritize experiential learning and metacompetency development as strategic foundations for preparing Gen Z to thrive in the VUCA workplace.